Strategy, Value and Risk A Guide to Advanced Financial Management - Rogers, Jamie (Palgrave Macmillan UK, 2013)
Updated and revised, the third edition frames strategy as delivering firm value in both the short and long term while maintaining a sustainable competitive advantage. These issues are examined through industry evolution, the rise of the information economy, financial analysis, corporate and quantitative finance, and risk management concepts